Suitable concentrations of brassinolide application enhances growth performance and saikosaponin biosynthesis by transcriptional activation of triterpenoid pathway genes in Bupleurum chinense DC - Shengwei Zhou; Shengwei Zhou; Shengwei Zhou; Shengwei Zhou; Linlin Yang; Linlin Yang; Linlin Yang; Linlin Yang; Jie Wan; Lu Chen; Lu Chen; Lu Chen; et al. (Frontiers in Plant Science)
The role of brassinolides (BRs) in regulating the synthesis of plant secondary metabolites has been recognized. However, the effect of brassinolides on the synthesis of saikosaponin in Bupleurum chinense DC. (B. chinense) is still unresolved, To address this knowledge gap, experiments were conducted in which different concentrations (0 mg/L as CK, 0.1 mg/L, 0.2 mg/L, and 0.4 mg/L) of BRs solution were sprayed on B. chinense taproot in the present study. We measured the growth indicators of each group of B. chinense, used quantitative real-time PCR (qRT-PCR) to determine the expression level of genes related to the biosynthesis of saikosaponin, used terpenoid-targeted metabolomics to determine the accumulation of saikosaponin, and verified the metabolomics results by HPLC. Following a 12-day treatment with the 0.2 mg/L BRs solution, the fresh and dry root weights, the taproot length, and the taproot diameter of B. chinense escalated by 60.35%, 60.11%, 25.17%, and 28.07% respectively, in comparison with the CK group. The expression of genes related to the biosynthesis of saikosaponin (HMGR, DXR, IPPI, FPS, SE, P450-2, and P450-3) significantly increased. Moreover, a terpenoid-targeted metabolomic investigation identified 27 distinct saikosaponins, inclusive of saikosaponin A and D, with a notable accumulation observed in 17 saikosaponins. The HPLC findings indicated that the contents of saikosaponin A and D elevated by 72.64% and 80.75% respectively when treated with 0.2 mg/L BRs solution. Conversely, the treatment of 0.4 mg/L BRs solution did not exhibit any significant alteration in the concentrations of saikosaponin A and D when compared to the CK group. In conclusion, the 0.2 mg/L BRs solution demonstrates a more pronounced regulatory impact on the synthesis of saikosaponin A and D. Our investigation revealed that the accumulation of these crucial medicinal bioactive compounds, saikosaponin A and D, can be enhanced through the application of a 0.2 mg/L BRs solution in the ecological cultivation of B. chinense.